Estimation of primary care treatment costs and treatment efficacy for people with Type 1 and Type 2 diabetes in the United Kingdom from 1997 to 2007 - Currie, C. J.; Gale, E. A. M.; Poole, C. D. (Diabetic medicine, 2010)
Diabet. Med. 27, 938–948 (2010) Aims  The purpose of this study was to characterize the financial cost and efficacy of primary care treatment for diabetes in the United Kingdom from 1997 to 2007. Methods  Retrospective data were analysed for people with Type 1 and Type 2 diabetes along with matched control subjects using data from The Health Improvement Network. Costs were attributed from published sources and adjusted for price inflation. Type 2 diabetes was analysed by five commonly used treatment regimens. Results  It was possible to identify 126 052 people for inclusion: 11 300 (8.9%) with Type 1 diabetes and 114 752 (91.1%) with Type 2. The overall mean prescribing costs per person per year (pppy) increased markedly for people with diabetes from 1997 to 2007: for Type 1, from £573 to £1014 pppy (+77%), and for Type 2, from £39 to £740 pppy (+89%). In 2007, diabetes‐treatment‐specific prescribing represented 57% of prescribing costs in Type 1 diabetes and 28% in Type 2 diabetes. In Type 2 diabetes there was a mean of 5.4 primary care consultations in 1997, increasing to 11.5 pppy in 2007 (+112%). In 1997 the total mean cost of primary care treatment for Type 2 diabetes was £602 pppy, increasing to £1080 in 2007. In Type 1 diabetes, the mean glycated haemoglobin decreased by 0.1% from 8.8% in 2001 to 8.7% in 2007; the corresponding change using insulin in Type 2 diabetes was also 0.1%. Greater improvement in blood pressure and lipids was evident. Conclusions  Over the 10 year period to 2007, diabetes‐related primary care adjusted costs increased considerably, whereas glycated haemoglobin values did not improve at all over the same period.